Analisis Dampak Penerapan Kebijakan Tarif Bea Masuk Terhadap Impor Gula di Indonesia: The Impact Analysis of Import Tariff Policies on The Import of Sugar in Indonesia - Inti, Ristani Widya; Rozci, Fatchur (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This research has the aim of analyzing and knowing the impact that has occurred on the applicable policies. This study uses a qualitative method through a literature review approach and descriptive analysis. The results showed that sugar imports were from 7 countries: India, Thailand, Brazil, Australia, South Korea, United Arab Emirates, Germany, and other countries. With the biggest sugar importers coming from India, Thailand, and Brazil. An import duty tariff policy in the Menperindak Decree (SK) No. 643/MPP/KEP/9/2002 describes the requirements for importing sugar. Thus, the impact is the emergence of policies for paying import duty tariffs on sugar imports.